HIV Status in Discordant Couples in Sub-Saharan Africa : A Systematic Review and Meta-Analysis - Eyawo, O.; de Walque, D.; Ford, N.; Gakii, G.; Lester, R. T.; Mills, E. J. (2012)
Background Most couples affected by HIV/AIDS in sub-Saharan Africa live in discordant relationships. Men are thought to be the index case in most relationships, and most social marketing and awareness campaigns are focused on men. We investigated serodiscordance in stable relationships to establish the gender balance of index-case infections. Methods We did a systematic review, random-effects meta-analysis, and meta-regression of published and unpublished studies enrolling discordant couples and assessed the proportion of men and women that were index cases. We repeated the analysis with data from demographic and health surveys (DHS) from the 14 countries that have documented the HIV status of couples. Our primary outcome was the total number of HIV discordant couples, including the proportion of HIV-positive women. Findings We included data from 27 cohorts of 13 061 couples and DHS data from 14 countries of 1145 couples. The proportion of HIV-positive women in stable heterosexual serodiscordant relationships was 47% (95% CI 43-52), which shows that women are as likely as men to be the index partner in a discordant couple. DHS data (46%, 41-51) and our sensitivity analysis (47%, 43-52) showed similar findings. Meta-regression showed that urban versus rural residence (odds ratio 0.31, 95% CI 0.22-0.39), latitude (beta coefficient 0.02, 0.023-0.034), gender equality (beta coefficient -0.42, -0.56 to -0.27), HIV prevalence (beta coefficient -0-037, -0.04 to -0.030), and older age (beta coefficient 0.20, 0.08-0.32) were associated with the proportion of female index cases. Interpretation Our study shows the need to focus on both sexes in HIV prevention strategies, such as promotion of condom use and mitigation of risk behaviours.